RELIGION AND LOCAL POLITICS: Exploring the Subcultures and the Political Participation of East Java NU Elites in the Post-New Order Era (State Islamic University (UIN) of Sunan Ampel Surabaya, 2010)
The history of the involvement of NU in politics cannot be separated from the elites of this organization in East Java. The variety of cultures that flourishes in the province strongly influences the nature and characteristics of the NU elites. This paper is an attempt to deal with the relationship between those subcultures and political participation. It focuses only on five subcultures, Mataraman, coastal areas, Arek, Madurese, and Pendalungan. The NU kiais are perceived by their followers to have played double roles as religious leaders (dealing with spiritual aspects) and community leaders (relating to socio-political aspects). Locality and its growing culture become a key factor. Locality makes a contribution to the growth of understanding about politics. Mataraman NU elites always keep their relationship with formal religious issues, and there is a tendency among them to separate religion from politics. In contrast, Madura, Pendalungan, Pesisiran (north coast), and Arek areas tend to combine religion and politics.